Effect of TED Talks on University Students' Speaking Skill Competency: A Meta-Analysis - Patty, Jusak (International Journal of Multidisciplinary Approach Research and Science, 2024)
This meta-analysis investigated the effectiveness of using TED Talks to improve speaking skills among university students. A comprehensive literature search identified 16 relevant experimental studies that compared speaking outcomes between groups using TED Talks and control groups. Results revealed an overall large, statistically significant positive effect (g = 1.521, p < 0.001), indicating that students who utilized TED Talks scored substantially higher on speaking measures than control groups. However, a high degree of heterogeneity (I2 = 97.5%) suggested variability in effectiveness across studies. When examined by country, substantial positive effects were found for Egypt (g = 5.579) and Saudi Arabia (g = 1.955), with high positive impacts in Indonesia (g = 0.889), Pakistan (g = 1.188), and Russia (g = 1.138). More modest gains around 0.3-0.7 standard deviations emerged for South Korea and Turkey, while China showed a negligible effect (g = 0.072). Despite some individual null/negative findings, this meta-analysis provides robust evidence that integrating TED Talks can substantially enhance university students' speaking proficiency, particularly in particular national contexts. Potential moderators influencing effectiveness and recommendations for optimizing TED Talk implementation are discussed.